(untitled) (Medical Forum Monthly, 2022)
Objective: To find the prevalence of various commonly occurring tongue anomalies like geographic tongue, median rhomboid glossitis, hairy tongue and fissured tongue in the patients visiting out-patient clinic in central Punjab. Study Design: Prospective Observational Study. Place and Duration of Study: This study was conducted at the Diagnostics and Oral Medicine Department of Islam dental college, Sialkot from October 2020 to July 2021 for a period of 12 months to measure the relative frequency of various tongue anomalies in adult population of central Punjab. Materials and Methods: 600 patients were examined in this study with an age range of 25-35 years. The examination was conducted in a quiet, comfortable and relaxed environment with the help of mouth mirror, natural light and gauze. The result was analyzed by using chi-square test in SPSS. Results: The prevalence of all tongue anomalies was 24.3% (4.8% geographic tongue, 1.75% median rhomboid glossitis, 0.8% hairy tongue, 11.8% Fissured tongue). Conclusion: The results of this study are near to some previous studies while contradict to some other studies as well. This study has shown the tongue anomalies are slightly more in males although the statistical difference is not significant. Moreover, it has also showed that age is not related to tongue anomalies.